On the rotation Boolean permutation. (2018) - Zhou, Yu
Internet of things need the encryption algorithm with a piece of small area with small-scale. This paper obtains some rotation Boolean permutations by the matrix of linear expressions, and constructs three methods of rotation nonlinear Boolean permutations. The sub-functions of the three permutations have some properties with three monomials, high degree and 2-algebra immunity. Finally, we derive the disjoint spectra Boolean functions.